Effect of Hyperthyroidism in Serum Samples Utilizing Cyclic Voltammetry - Najeb, Haydar Basim (American Journal of Biomedicine and Pharmacy, 2025)
Hyperthyroidism is a speeds up the body's metabolism by excessive production of thyroid hormones, which may lead to various physiological changes in the body. The aim of this study was to examine the effect of hyperthyroidism on the oxidative profile of serum samples using cyclic voltammetry, and to evaluate changes in redox behavior, identify potential biomarkers, and the mechanisms of oxidative stress in hyperthyroidism. The influence of serum samples was obtained from individuals diagnosed with hyperthyroidism and healthy controls by using a cyclic voltammetry. samples of 30 patients of hyperthyroidism showed significant differences in oxidative stress by enhanced the current peak compared to the control group, indicating altered redox properties. Specific oxidation stress parameters were found to be elevated in the hyperthyroidism patients against to different diseases suffered these patients by analyses each of T3, T4, TSH, FBG, HbA1C, TC, TG, and HDL. The oxidative stress of the hyperthyroidism of the patients can be treated by ascorbic acid which acts as anti-oxidative reagent. The identified biomarkers and mechanistic understanding gained from this research could contribute to a better understanding of the role of oxidative stress in the pathophysiology of hyperthyroidism